Pemahaman Peran Pendidikan Pelayaran dalam Meningkatkan Kinerja Keagenan Kapal - Nisa, Hanifah Aulia; Wirza, Elfira (Politeknik Pelayaran Sumatera Barat, 2025)
The maritime industry requires highly competent human resources to ensure the effectiveness and efficiency of ship agency services. Maritime education plays a crucial role in equipping prospective ship agents not only with technical knowledge and practical skills, but also with essential non-technical competencies such as communication, leadership, adaptability, and problem-solving abilities. This study aims to analyze the role of maritime education in improving the performance of ship agency services, particularly in the context of modern challenges such as digitalization, automation, environmental sustainability, and increasingly complex global trade dynamics. The research applies a qualitative method with a literature review approach, examining scientific articles, institutional reports, and empirical studies published between 2020 and 2025. Findings indicate that maritime education contributes significantly to enhancing the professionalism and performance of ship agents through the integration of updated curricula, practical vocational internships, digital literacy programs, and the inclusion of green shipping awareness in learning processes. Moreover, collaboration between educational institutions, government bodies, and maritime industries is identified as a key driver in aligning educational outcomes with market demands. Educational policies that adapt to technological and environmental transitions are proven to increase employability, service quality, and competitiveness of ship agents. In conclusion, strengthening maritime education not only improves the operational effectiveness of ship agencies but also ensures their resilience and relevance in the rapidly evolving global maritime service sector.